FRI0425 Serological Markers and Their Correlation with Disease Activity Indexes and Imaging in Patients with Early Axial Spondyloarthritis (Italian Center of Space Study). (15th July 2016) - Lorenzin, M.; Ortolan, A.; Frallonardo, P.; Vio, S.; Oliviero, F.; Zaninotto, M.; Cosma, C.; Lacognata, C.; Punzi, L.; Ramonda, R.
Abstract : Background: Recently studies have focused on the role of new markers to diagnose early axial spondyloarthritis (axSpA), to evaluate disease activity (DA) and to predict patients (pts) at higher risk for a worse outcome. Common biomarkers, erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) are often ineffective in assessing DA. Objectives: To evaluate some biomarkers and their correlation with clinical parameters, DA indexes and imaging in pts with early axSpA. Methods: Sixty pts with low back pain (≥3 months, ≤2 years, onset ≤45 years) attending the SpA-UOC Rheumatology of Padua (SpondyloArthritis-Caught-Early SPACE study), were studied following a protocol including physical examination, questionnaires', lab tests, X-rays and MRI of spine and sacroiliac joints (SIJ)at baseline.An experienced rheumatologist made axSpA diagnosis according to ASAS criteria. The DA and physical functioning were assessed using: Bath Ankylosing Spondylitis Metrology Index (BASMI); Maastricht Ankylosing enthesitis Spondilities Score (MASES); Bath Ankylosing Spondylitis Disease Activity Index (BASDAI); Bath Ankylosing Spondylitis Functional Index (BASFI); Ankylosing Spondylitis disease activity score (ASDAS); Visual Analogue Scale (VAS pain); VAS night pain; VAS disease activity;Bath Ankylosing Spondylitis Patient Global Score (BASG1); BASG2; Health Assessment Questionnaire (HAQ); ESR; serum ultrasensitive CRP (hs-CRP); matrix metalloproteinase (MMP3); interleukin (IL) IL-22, IL-17, IL-23.Positive spine and SIJ MRI images were scored independently by 2 readers using the Spondyloarthritis Research Consortium of Canada (SPARCC) method; the spine and SIJ X-rays images were scored using mSASSS and NY-criteria. After the X-rays and MRI images of all pts were read, they were classified into the following cohorts: pts with signs of radiographic sacroiliitis (r-axSpA), pts without signs of radiographic sacroiliitis but with signs of sacroiliitis on SIJ-MRI (nr-axSpA MRI SIJ+), pts without signs of sacroiliitis on MRI and X-rays (nr-axSpA MRI SIJ-).The Spearman test and Kruskal Wallis test were used to compare all indexes in these cohorts. Results: There was a significant difference between the three cohorts with regard to the prevalence of radiographic sacroiliitis, active sacroiliitis on MRI and the SPARCC SIJ score (Table 1 ). There were no differences in these groups in IL-17, IL-22, IL-23, MMP-3 and hsCRP. ILs remained below detection value in all cohorts. The correlation of IL-17 and IL-23 with other indexes was not significant. There was instead a correlation between IL-22 and some clinical indexes (BASFI, BASG1, HAQ, VAS pain). The correlation between mSASSS and MMP3 and hsCRP was an interesting finding. Conclusions: ILs, MMP-3 and hsCRP values were not significantly increased in any of the study groups and were not related to radiographic SIJ involvement or to clinical and DA indexes. This finding can probably be explained by the fact that pts had early stage axSpA and by the small sample size. Further studies are needed to analyze the validity and reproducibility of these biomarkers in early axSpA. Disclosure of Interest: None declared